Mechanical properties of high strength concrete at high temperature loading - Johari, Zuraimi (2005)
The research effort aim characterized the mechanical behavior of high strength concrete at high temperature loading. Mechanical behaviors of two different type of concrete were measured after heated to 200 degree celcius, 400 degree celcius, 800 degree celcius and 1000 degree celcius. The average compressive strength of these two types of concrete before being too exposed to the high temperature is 30MPa and 60MPa. The following physical behaviors were measured for each concrete specimen prior to high temperature exposure: physical dimension, mass (initial mass, heated mass and total mass loss) and longitudinal resonance frequency (before and after heating). Before heating specimens until the selected temperature, a baseline data or control data set was generated for each type of concrete after exposure to a nominal room temperature (25 degree celcius). The selected temperatures were accomplished by placing the specimens into a low temperature electrical furnace for temperature below than 3000C and used high temperature electrical furnace for temperature greater than 300 degree celcius. Then the specimens will heat with rate of heating 200 degree celcius per hour or 50C per minute until reached steady state condition at one of selected temperature. Specimen will heat with a total heating period of 7 hours before cooled to room temperature for 24 hours. The specimens were weighed and resonance frequency was measured again (after heating). The compressive strength of each specimen was measured. Result from this research may be useful for assessing post fire behavior properties of high strength concrete.